Re-use of COVID-19 waste facemasks for modification of Nigeria’s naturally occurring bitumen for road construction - Bala Musa; Kenneth Tutu; Yaw Tuffour (Journal of Construction Project Management and Innovation, 2024)
Nigeria currently imports bitumen for road construction despite the presence of a significant amount of naturally occurring bitumen (NOB) in Ondo state. The use of facemasks during the COVID-19 pandemic has led to environmental challenges due to their non-biodegradable and harmful nature. This study explores the potential of utilising waste facemasks in modifying NOB for road paving in Nigeria. The physiochemical properties of NOB were determined, and tests were conducted to assess its suitability for road construction. The results showed that the neat NOB had high penetration, low softening point, and high viscosity, making it unsuitable for road construction in Nigeria’s tropical region. However, the modified NOB, when blended with waste facemasks, exhibited reduced penetration and increased softening point, aligning with the AC-10 grade bitumen requirements. Further testing using the Dynamic Shear Rheometer (DSR) is recommended to determine the rheological properties of the modified NOB. This study is the first of its kind to explore the use of waste facemasks in modifying naturally occurring bitumen for road construction. It proposes a novel solution that not only addresses the environmental issues associated with waste facemasks but also offers a sustainable alternative to imported bitumen. Future works include long-term performance studies, comparative evaluations, environmental impact assessments, and scaling-up studies to assess the feasibility and practicality of implementing this approach on a larger scale.